Effects of extreme meteorology in Seville during the 18th century: defense mechanisms against droughts and floods of the Guadalquivir - García-Barrón, Leoncio; García-Cuadri, Mª Rocío; García-Cuadri, Luis Antonio (Revista de Estudios Andaluces, 2024)
The southwest of the Iberian Peninsula is subject to irregular rainfall patterns with recurring opposite events, periods of drought or intense rain. Based on documentary sources, in the context of the particular hydrological conditions of the city and its urban protection system, the corresponding impacts of the Guadalquivir River in Seville during the 18th century are examined. Events that reveal vulnerability to extreme weather events are described. This has allowed us to prepare the annual water risk index. From its quantification, the temporal evolution throughout the 18th century is obtained. Irregularly distributed, variability is observed, in which the effects of drought are more frequent in the first half of the century and floods in the final decades.